The efficacy of velar adhesion in unilateral cleft lip and palate patients: Cleft width and otitis media with effusion - Miki Kashiwagi; Hideto Saijo; Sachi Oshima; Shota Ichikawa; Rika Narita; Kazuto Hoshi (PLoS ONE, 2025)
Background Cleft lip and palate (CLP) is one of the most common congenital anomalies, affecting ~1 in 700 births worldwide. Patients with CLP often experience functional impairments due to the cleft palate, particularly related to feeding and speech. Surgical interventions are essential for addressing these issues, yet no standardized surgical procedure exists. Velar adhesion (VA) is a technique used to reduce the cleft width prior to a palatoplasty, potentially improving surgical outcomes, but its effectiveness remains unclear. Objective The impact of VA on cleft-width reduction and the incidence of otitis media with effusion (OME) were evaluated in patients with unilateral cleft lip and palate (UCLP). Patients and methods The cases of 45 patients with UCLP who underwent a palatoplasty at the University of Tokyo Hospital between January 2013 and December 2023 were analyzed retrospectively. We divided the patients into two groups: those who underwent VA during lip repair (VA group) and those who did not (non-VA group). The cleft width and alveolar cleft width were measured at birth, lip repair, and palatoplasty. The presence of OME was assessed the day before the palatoplasty. Pearson’s chi-square test and the two-tailed t-test were applied. Results Significant cleft-width reduction was observed in the VA group compared to the non-VA group at the time of palatoplasty (4.58 mm vs. 6.55 mm, p < 0.01). The incidence of OME was significantly lower in the VA group (60.00%) versus the non-VA group (90.91%, p < 0.01). No significant between-group differences were identified for the alveolar cleft width or maxillary growth. Conclusion VA significantly reduces the cleft width at the junction of the hard and soft palates, and it may decrease the incidence of otitis media with effusion in patients with UCLP. VA is a straightforward procedure with potential benefits for improving palatoplasty outcomes and mitigating complications such as OME.